Factors Affecting the Incidence of Stunting in Toddlers in the Working Area of the UPTD Health Center, Rawat Lagari Hospital Nabire Regency - Natan Pigome; Nur Al-faida; Bau Kanang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background:Stunting reflects the condition of children under the age of five, due to malnutrition especially in the first 1000 days of life (HPK), children are very short for their age. In Indonesia, stunting is a major and major problem that is being faced. Toddlers are children over one year old and children under 5 years old. Objective: To determine the factors associated with stunting in toddlers in the working area of ​​the Lagari Inpatient Health Center UPTD, Nabire Regency. Method: The type of research used in this study is quantitative and the design used is observational analytic. Results: analysis test using the chi-square test p-value> 0.05, 0.82 indicates that there is no relationship between education and stunting in toddlers. Analysis test using the chi-square test p-value> 0.05, namely 0.09 indicates that there is no relationship between work and stunting in toddlers. Analysis test using the chi-square test p-value <0.05, namely 0.04 indicates that there is a relationship between income and stunting in toddlers. Analysis test using chi-square test p-value <0.05, which is 0.05 indicates that there is a relationship between knowledge and the incidence of stunting in toddlers. Analysis test using chi-square test p-value <0.05, which is 0.05 indicates that there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers. Conclusion: Factors that influence stunting in toddlers include: education, employment, income, knowledge and exclusive breastfeeding. There is no relationship between education and employment with the incidence of stunting in toddlers, and there is a relationship between employment, knowledge and exclusive breastfeeding with the incidence of stunting in toddlers. Suggestion: Create a program on stunting, especially the factors that influence stunting to reduce stunting rates and need to increase counseling activities on stunting for mothers of toddlers to increase awareness and understanding of stunting.